Synaptic Vesicle Glycoprotein 2C: a role in Parkinson’s disease - Chang, Chu Hua; Lim, Kah Leong; Foo, Jia Nee (Frontiers in Cellular Neuroscience, 2024)
Synaptic Vesicle Glycoprotein 2C (SV2C), characterised by its selective expression in discrete brain regions such as the midbrain, has recently emerged as a promising player in Parkinson's Disease (PD) -a debilitating neurodegenerative disorder affecting millions worldwide. This review aims to consolidate our current understanding of SV2C's function, its involvement in PD pathogenesis, and to evaluate its potential as a therapeutic target. Integrating previous findings of SV2C, from genetics to molecular studies, and drawing on insights from the largest East Asian genome-wide association study that highlights SV2C as a novel risk factor for PD, we explore the potential pathways through which SV2C may influence the disease. Our discussion extends to the implications of SV2C's role in synaptic vesicle trafficking, neurotransmitter release, and α-synuclein homeostasis, thereby laying the groundwork for future investigations that could pave the way for novel therapeutic strategies in combating PD.